The social welfare during the classic Peronism. The expansion of health services to rural areas of the municipalities in the province of Mendoza (1946-1955) - Hirschegger, Ivana (Centro de Historia Argentina y Americana, 2010)
With the arrival of the Peronism to the government reforms took place in relation to the organization and functioning of the system of public health. But beyond his successes or failures, the care and the preservation of the health of the population, including that of the most remote and backward zones of the interior of the country, was one of the principal goals of the government of Juan Domingo Perón. From this, our central objective is to study the sanitary policies in the municipalities of the province of Mendoza during the period 1946-1955, attending to two aspects: the first one of them, related to the role of the national and provincial government in the execution of this public politics, and the second one, with the results, achievements and effects of the same one in the departments mendocinos. This empirical study, in which programs are arranged by results, will allow to know then the royal fulfillment of the aims established by the Peronism.